Pengembangan Alat Peraga Ropintri Pada Siswa SMAS Kelas X Untuk Meningkatkan Hasil Belajar Siswa - Rambe, Isnaini Halimah; Jelita, Adilla; Sembiring, Metrilitna Br (TIN: Terapan Informatika Nusantara, 2024)
Based on observation, the researcher noted that the grade X teacher at SMA Swasta Al-Washliyah 1 Medan did not use media or teaching aids in teaching trigonometry. The learning process only relies on textbooks from the government, Student Worksheets (LKS), and the lecture method, so it is less interesting and tends to be boring. The material presented is also limited to printed mathematics books, without any teaching aids or other learning media that can help improve the effectiveness of learning. This research aims to develop learning media in the form of ropintri teaching aids at Al-Washliyah 1 Medan Senior High School that are valid, practical, and effective to improve student learning outcomes. This type of research is the development of Thiagarajan's 4D model (define, design, develop, disseminate). The sample in this study were 28 students of class X-A SMAS Al-Washliyah 1 Medan. The techniques used in data collection are using questionnaire validation sheets, practicality instruments and test instruments. From the trial results obtained the results of ropintri props have met the criteria very valid based on expert assessment of 90.70%; ropintri props have met the criteria very practical based on a response questionnaire of 90.9%. The ropintri teaching aids met the criteria of being very effective from student learning outcomes of 96.42% with a gain increase of 0.6364 in the medium category. It can be concluded that ropintri teaching aids are valid, practical, and effective in improving student learning outcomes.